2017
DOI: 10.1128/jvi.02082-16
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Pol Mutations Selected by HLA-B*52:01-C*12:02 Protective Haplotype-Restricted Cytotoxic T Lymphocytes Causes Low Plasma Viral Load Due to Low Viral Fitness of Mutant Viruses

Abstract: HLA-B*52:01-C*12:02, which is the most abundant haplotype in Japan, has a protective effect on disease progression in HIV-1-infected Japanese individuals, whereas HLA-B*57 and -B*27 protective alleles are very rare in Japan. A previous study on HLA-associated polymorphisms demonstrated that the number of HLA-B*52:01-associated mutations at four Pol positions was inversely correlated with plasma viral load (pVL) in HLA-B*52:01-negative individuals, suggesting that the transmission of HIV-1 with these mutations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 40 publications
2
18
0
Order By: Relevance
“…Next, 100,000 PBMCs from HLA-B*35:01 + HIV-1-infected individuals were plated in each well in the ELISPOT plate along with a concentration of 100 nM of each of 16 known HLA-B*35:01-resticted epitope peptides [ 31 , 33 , [36] , [37] , [38] , [39] , [40] , [41] , [42] ]. We calculated the number of CD8 + T cells plated in each well containing 100,000 PBMCs by using the frequency of CD8 + T cells amongst PBMCs and determined spots/10 6 CD8 + T cells in each well [ 35 , [43] , [44] , [45] ]. The number of spots for each peptide-specific T cell response was finally calculated by subtracting the number of spots in wells without peptides.…”
Section: Methodsmentioning
confidence: 99%
“…Next, 100,000 PBMCs from HLA-B*35:01 + HIV-1-infected individuals were plated in each well in the ELISPOT plate along with a concentration of 100 nM of each of 16 known HLA-B*35:01-resticted epitope peptides [ 31 , 33 , [36] , [37] , [38] , [39] , [40] , [41] , [42] ]. We calculated the number of CD8 + T cells plated in each well containing 100,000 PBMCs by using the frequency of CD8 + T cells amongst PBMCs and determined spots/10 6 CD8 + T cells in each well [ 35 , [43] , [44] , [45] ]. The number of spots for each peptide-specific T cell response was finally calculated by subtracting the number of spots in wells without peptides.…”
Section: Methodsmentioning
confidence: 99%
“…A study in an HIV-1 clade C-infected African cohort showed that Pol-specific T-cell responses were not associated with a significant reduction in plasma viral load (pVL), whereas Gag-specific responses significantly correlated with lower pVL (10). In contrast, a study of clade B-infected treatment-naive Japanese individuals demonstrated that in addition to Gag-specific T cells, Pol-specific T cells also had a strong ability to suppress HIV-1 replication in vivo (2022).…”
Section: Introductionmentioning
confidence: 96%
“…HLA-B ∗ 57:01 is known to strongly decrease the rate of disease progression, however, across multiple continents; it has been shown that HIV is developing an escape mutation, I135X, which attenuates control (Kawashima et al, 2009). Similarly, the protective allele HLA-B ∗ 52:01-C ∗ 12:02 is associated with decreased viral load in Japan due to the development of escape mutations in the pol gene of HIV which causes poor viral fitness (Murakoshi et al, 2017). These escape mutations allow the virus to evade HLA detection and change the dynamics of disease progression, albeit at the cost of viral fitness.…”
Section: Hiv Genetic Impact On Hiv Pathogenesismentioning
confidence: 99%